(untitled) (Research, Society and Development, 2021)
The project was carried out in the Sítio Redinha Community and lasted for 05 months. At first, the members selected the main existing fake news, in order to demystify them based on scientific data, later they made Videos and Folders, which were published weekly. The main means of disseminating the materials were social networks, such as WhatsApp, which had the number made available to the head of the community, so that, through this, information could be shared, as well as Facebook and Instagram. Therefore, the project was successful in its actions, since the target audience had access to knowledge about Covid-19, mitigating the effect of false news related to the use of herbal medicines and medicinal plants during the pandemic.